Rekonstruksi Teori Sibernetik Norbert Wiener sebagai Paradigma Sistemik Peningkatan Mutu Pendidikan dalam Perspektif Psikologi Pendidikan - Sergius Lay; Junita Hulu; Velika Carles Farma Putri Bate'e; Kristiani Putri Lase (Journal New Light, 2026)
Educational quality serves as a central indicator of the effectiveness of instructional systems in achieving educational objectives. However, prevailing linear and less adaptive instructional practices reveal weaknesses in feedback-based regulatory mechanisms within educational systems. This article aims to reconstruct Norbert Wiener’s cybernetic theory as a systemic paradigm for improving educational quality within the framework of educational psychology. The study employs a qualitative approach using a library research design through content analysis and conceptual synthesis of relevant primary and secondary sources. The findings indicate that the principles of control and communication in cybernetic theory can be integrated with self-regulation and formative assessment concepts to develop an adaptive learning system based on dual-loop regulation. This study proposes the Cybernetic Feedback-Based Educational Quality Improvement Model (MPM–SUS), consisting of five components: input, interactive regulatory process, output, dual feedback mechanisms, and strategic adaptation. The novelty lies in operationalizing classical cybernetic theory into a modern educational psychology framework by integrating micro (classroom), meso (school), and macro (policy) regulatory levels. Educational quality is thus conceptualized as the outcome of a structured, data-driven, and continuous control cycle.